A trifluoromethyl-grafted ultra-stable fluorescent covalent organic framework for adsorption and detection of pesticides. Issue 47 (19th November 2020) - Zhao, Yuxiang; Sui, Zhuyin; Chang, Zhaosen; Wang, Shunli; Liang, Ying; Liu, Xin; Feng, Lijuan; Chen, Qi; Wang, Ning
Abstract : A fluorine-rich ultra-stable fluorescent covalent organic framework for adsorption and detection of pesticides was designed and prepared via the Povarov reaction in a flask. Abstract : A fluorine-rich covalent organic framework, COF-(CF3 )2, was designed and prepared by post-functionalization via the Povarov reaction in a flask in order to take up fluorinated pesticides. Compared with those obtained by a synthetic method performed in a Pyrex tube, the as-prepared COFs in our process not only possess higher specific surface areas, but also can be obtained on a large scale. It's worth noting that COF-(CF3 )2 exhibits strong chemical stability even in KMnO4 or NaBH4 solutions, which is highly beneficial for its practical applications. Considering the strong and selective fluorine–fluorine interactions, COF-(CF3 )2 was used for the uptake of fluorinated pesticides and showed higher adsorption capacities for trifluralin (151 mg g −1 ) and fipronil (171 mg g −1 ). We also found unexpectedly that COF-(CF3 )2 possesses strong fluorescence due to the enhanced conjugated system via cycloaddition functionalization. This unique property can be applied in detecting trifluralin through fluorescence quenching induced by their interaction.